Environmental Risk Assessment and Management in Oil Platform Construction Phase Activities: A Case Study - Younesi, A.; Rahmani, R.; Jaafari, J.; Mahdavi, Y. (Engineering, Technology & Applied Science Research, 2017)
The construction phase is one of the very risky stages engaged in oilfields, which usually involves minor to severe human, financial, and environmental damages. It includes a major part of lost working times, and in recent years, along with the development of oilfields and oil platform construction activities in Iran, hazardous risks and events have occurred and have been recorded. Therefore, this study aims to reduce the negative effects of the risks engaged in oil platform construction activities in the region under study, i.e. the Abuzar oilfield. The indexing system method, along with determining the importance index, effect, and frequency of occurrence, was used in this study to evaluate the environmental risks of oil platform construction activities in Abuzar oilfield. First, the project activities were identified and then, the effect of desired activities on environmental aspects (water, air, soil, human, waste production, and noise) was investigated. For quantitative estimation of risk values through interviewing the experts and using the tables of intensity, effect, and frequency of event occurrence, were calculated based on the formula governing the effect of different activities on the environment, and the risk value was determined. The research findings indicated that most of the environmental risks are in the range of average risks (72.9%) however 20.2% are in the range of low risks and 6.9% are in the range of high risks. Finally, considering experts’ viewpoints, management solutions were proposed to reduce the risk of activities, and the risk priority numbers were calculated after performing the corrective actions.